(untitled) (Chemical Engineering Research Bulletin, 2011)
Biosorption of heavy metals can be an effective process for the removal of toxic heavy metals present in the wastewater. An attempt is made in the present investigation to remove Cd2+ ions from aqueous solutions using B.subtilis. Batch experiments were carried out for Cd2+ removal over a wide range of operating conditions. It has been noticed that the Cd2+ removal capacity dependent on the initial pH and the initial Cd2+ concentration. Experimental data were analysed with kinetics and isotherm models. It has been observed that the pseudo second order kinetics and Freundlich isotherm equilibrium model fit well with the present data. The FTIR analysis of bacterial biomass revealed the presence of amino, carboxyl, hydroxyl and carbonyl groups, which are responsible for biosorption of Cd2+ metal ions. The results indicated that the biomass of B.subtilis is an efficient bioaccumulant for the removal of Cd2+ ions from aqueous solutions. Key words: Biosorption; Cd2+ removal; Kinetics; Isotherms; Bacillus subtilis-live and dead DOI: http://dx.doi.org/10.3329/cerb.v15i1.6618 Chemical Engineering Research Bulletin 15 (2011) 18-24